Copyright (c) 1989 Association of Mizar Users
environ vocabulary ARYTM, ARYTM_3, RELAT_1, ARYTM_1, ABSVALUE, SQUARE_1; notation TARSKI, SUBSET_1, ORDINAL1, NUMBERS, XCMPLX_0, XREAL_0, ABSVALUE; constructors REAL_1, ABSVALUE, XCMPLX_0, XREAL_0, XBOOLE_0; clusters XREAL_0, REAL_1, NUMBERS, ARYTM_3, ZFMISC_1, XBOOLE_0; requirements REAL, NUMERALS, SUBSET, BOOLE, ARITHM; definitions TARSKI, REAL_1, XREAL_0; theorems AXIOMS, REAL_1, ABSVALUE, XREAL_0, XCMPLX_0, XCMPLX_1; begin reserve a,b,c,x,y,z for real number; canceled; theorem 1 < x implies 1/x < 1 proof assume A1: 1<x; then A2: 0<x by AXIOMS:22; then 0<x" by REAL_1:72; then 1*x"<x*x" by A1,REAL_1:70; then 1"*(1*x")<1"*1 by A2,XCMPLX_0:def 7; hence 1/x < 1 by XCMPLX_0:def 9; end; canceled 8; theorem Th11: x < y implies 0 < y - x proof assume x < y; then x + 0 < y; hence thesis by REAL_1:86; end; theorem Th12: x <= y implies 0 <= y - x proof assume x <= y; then x - x <= y - x by REAL_1:49; hence 0 <= y - x by XCMPLX_1:14; end; canceled 6; theorem Th19: 0 <= x & 0 <= y implies 0 <= x*y proof assume 0 <= x & 0 <= y; then x*0 <= x*y by AXIOMS:25; hence 0 <= x*y; end; theorem x <= 0 & y <= 0 implies 0 <= x*y proof assume x <= 0 & y <= 0; then x*0 <= x*y by REAL_1:52; hence 0 <= x*y; end; theorem Th21: 0 < x & 0 < y implies 0 < x*y proof assume 0 < x & 0 < y; then x*0 < x*y by REAL_1:70; hence 0 < x*y; end; theorem Th22: x < 0 & y < 0 implies 0 < x*y proof assume x < 0 & y < 0; then x*0 < x*y by REAL_1:71; hence 0 < x*y; end; theorem Th23: 0 <= x & y <= 0 implies x*y <= 0 proof assume A1: 0 <= x & y <= 0; then 0 <= -y by REAL_1:26,50; then 0 <= x*(-y) by A1,Th19; then 0 <= -(x*y) by XCMPLX_1:175; hence x*y <= 0 by REAL_1:26,50; end; theorem Th24: 0 < x & y < 0 implies x*y < 0 proof assume A1: 0 < x & y < 0; then 0 < -y by REAL_1:66; then 0 < x*(-y) by A1,Th21; then 0 < -(x*y) by XCMPLX_1:175; hence x*y < 0 by REAL_1:66; end; theorem 0 <= x*y implies 0 <= x & 0 <= y or x <= 0 & y <= 0 by Th24; theorem 0 < x*y implies 0 < x & 0 < y or x < 0 & y < 0 proof assume A1: 0 < x*y; then x <> 0; then 0 < x or x < 0; hence thesis by A1,Th23; end; theorem Th27: 0 <= a & 0 <= b implies 0 <= a/b proof assume that A1: 0 <= a and A2: 0 <= b; per cases by A2; suppose 0 = b; then a/b = a*0" by XCMPLX_0:def 9 .= a*0; hence thesis; suppose 0 < b; then 0 < b" by REAL_1:72; then 0 <= 1/b by XCMPLX_1:217; then 0 <= a*(1/b) by A1,Th19; then 0 <= (a*1)/b by XCMPLX_1:75; hence 0 <= a/b; end; canceled; theorem Th29: 0 < x implies y - x < y proof assume 0 < x; then -x < 0 by REAL_1:26,50; then y + -x < y + 0 by REAL_1:53; hence y - x < y by XCMPLX_0:def 8; end; scheme RealContinuity { P[set], Q[set] } : ex z st for x,y st P[x] & Q[y] holds x <= z & z <= y provided A1: for x,y st P[x] & Q[y] holds x <= y proof set X = { z where z is Element of REAL : P[z] }; set Y = { z where z is Element of REAL : Q[z] }; A2: X c= REAL proof let x be set; assume x in X; then ex z being Element of REAL st z = x & P[z]; hence thesis; end; Y c= REAL proof let x be set; assume x in Y; then ex z being Element of REAL st z = x & Q[z]; hence thesis; end; then reconsider X, Y as Subset of REAL by A2; for x,y being real number st x in X & y in Y holds x <= y proof let x,y be real number; assume x in X & y in Y; then (ex z being Element of REAL st z = x & P[z]) & ex z being Element of REAL st z = y & Q[z]; hence x <= y by A1; end; then consider z being real number such that A3: for x,y being real number st x in X & y in Y holds x <= z & z <= y by AXIOMS:26; take z; let x,y; assume A4: P[x] & Q[y]; x is Element of REAL & y is Element of REAL by XREAL_0:def 1; then x in X & y in Y by A4; hence x <= z & z <= y by A3; end; definition let x,y; func min(x,y) -> real number equals :Def1: x if x <= y otherwise y; correctness; commutativity by AXIOMS:21; idempotence; func max(x,y) -> real number equals :Def2: x if y <= x otherwise y; correctness; commutativity by AXIOMS:21; idempotence; end; definition let x,y be Element of REAL; redefine func min(x,y) -> Element of REAL; coherence by XREAL_0:def 1; redefine func max(x,y) -> Element of REAL; coherence by XREAL_0:def 1; end; canceled 4; theorem Th34: min(x,y) = (x + y - abs(x - y)) / 2 proof now per cases; suppose A1: x <= y; then 0 <= y - x by Th12; then A2: 0 <= -(x-y) by XCMPLX_1:143; thus min(x,y) = x by A1,Def1 .= (x+x)/2 by XCMPLX_1:65 .= (((x+y)-y)+x)/2 by XCMPLX_1:26 .= ((x+y)- (y - x))/2 by XCMPLX_1:37 .= ((x+y)- -(x - y))/2 by XCMPLX_1:143 .= ((x+y)-abs(-(x - y)))/2 by A2,ABSVALUE:def 1 .= ((x+y)-abs(x - y))/2 by ABSVALUE:17; suppose A3: y <= x; then A4: 0 <= x - y by Th12; thus min(x,y) = y by A3,Def1 .= (y+y)/2 by XCMPLX_1:65 .= (x+y-x+y)/2 by XCMPLX_1:26 .= ((x+y)- (x - y))/2 by XCMPLX_1:37 .= ((x+y)-abs(x-y))/2 by A4,ABSVALUE:def 1; end; hence thesis; end; theorem Th35: min(x,y) <= x proof x <= y or not x <= y; hence min(x,y) <= x by Def1; end; canceled 2; theorem Th38: min(x,y) = x or min(x,y) = y proof assume min(x,y) <> x; then not x <= y by Def1; hence min(x,y) = y by Def1; end; theorem Th39: x <= y & x <= z iff x <= min(y,z) proof thus x <= y & x <= z implies x <= min(y,z) by Th38; min(y,z) <= y & min(y,z) <= z by Th35; hence thesis by AXIOMS:22; end; theorem min(x,min(y,z)) = min(min(x,y),z) proof per cases by AXIOMS:22; suppose x <= y & x <= z; then min(x,y) = x & min(x,z) = x & (min(y,z) = y or min(y,z) = z) by Def1, Th38; hence thesis; suppose y <= x & y <= z; then min(x,y) = y & min(y,z) = y by Def1; hence thesis; suppose z <= y & z <= x; then min(y,z) = z & min(x,z) = z & (min(x,y) = x or min(x,y) = y) by Def1, Th38; hence thesis; end; canceled 4; theorem Th45: max(x,y) = (x + y + abs(x-y)) / 2 proof now per cases; suppose A1: y <= x; then A2: 0 <= x - y by Th12; thus max(x,y) = x by A1,Def2 .= (x+x)/2 by XCMPLX_1:65 .= (x+y-y+x)/2 by XCMPLX_1:26 .= (x+y+ -y+x)/2 by XCMPLX_0:def 8 .= (x+y+ (x + -y))/2 by XCMPLX_1:1 .= ((x+y)+ (x - y))/2 by XCMPLX_0:def 8 .= ((x+y)+abs(x-y))/2 by A2,ABSVALUE:def 1; suppose A3: x <= y; then 0 <= y - x by Th12; then A4: 0 <= -(x-y) by XCMPLX_1:143; thus max(x,y) = y by A3,Def2 .= (y+y)/2 by XCMPLX_1:65 .= (((x+y)-x)+y)/2 by XCMPLX_1:26 .= ((x+y)-(x-y))/2 by XCMPLX_1:37 .= ((x+y)+ -(x - y))/2 by XCMPLX_0:def 8 .= ((x+y)+abs(-(x-y)))/2 by A4,ABSVALUE:def 1 .= ((x+y)+abs(x-y))/2 by ABSVALUE:17; end; hence thesis; end; theorem Th46: x <= max(x,y) proof y <= x or not y <= x; hence x <= max(x,y) by Def2; end; canceled 2; theorem Th49: max(x,y) = x or max(x,y) = y proof assume max(x,y) <> x; then not y <= x by Def2; hence max(x,y) = y by Def2; end; theorem y <= x & z <= x iff max(y,z) <= x proof thus y <= x & z <= x implies max(y,z) <= x by Th49; y <= max(y,z) & z <= max(y,z) by Th46; hence max(y,z) <= x implies y <= x & z <= x by AXIOMS:22; end; theorem max(x,max(y,z)) = max(max(x,y),z) proof per cases by AXIOMS:22; suppose x <= y & x <= z; then max(x,y) = y & max(x,z) = z & (max(y,z) = z or max(y,z) = y) by Def2, Th49; hence thesis; suppose y <= x & y <= z; then max(x,y) = x & max(y,z) = z by Def2; hence thesis; suppose z <= y & z <= x; then max(y,z) = y & max(x,z) = x & (max(x,y) = y or max(x,y) = x) by Def2, Th49; hence thesis; end; canceled; theorem min(x,y) + max(x,y) = x + y proof thus min(x,y) + max(x,y) = (x + y - abs(x-y)) / 2 + max(x,y) by Th34 .= (x + y - abs(x-y)) / 2 + (x + y + abs(x-y)) / 2 by Th45 .= ((x + y - abs(x-y)) + (abs(x-y) + (x + y))) / 2 by XCMPLX_1:63 .= (x + y + (x + y)) / 2 by XCMPLX_1:28 .= x + y by XCMPLX_1:65; end; theorem Th54: max(x,min(x,y)) = x proof per cases; suppose x <= y; hence max(x,min(x,y)) = max (x,x) by Def1 .= x; suppose A1: y <= x; hence max(x,min(x,y)) = max (x,y) by Def1 .= x by A1,Def2; end; theorem Th55: min(x,max(x,y)) = x proof per cases; suppose A1: x <= y; hence min(x,max(x,y)) = min(x,y) by Def2 .= x by A1,Def1; suppose y <= x; hence min(x,max(x,y)) = min(x,x) by Def2 .= x; end; theorem min(x,max(y,z)) = max(min(x,y),min(x,z)) proof per cases by AXIOMS:22; suppose A1: x <= y & x <= z; y <= max(y,z) by Th46; then x <= max(y,z) by A1,AXIOMS:22; hence min(x,max(y,z)) = x by Def1 .= max(min(x,y),x) by Th54 .= max(min(x,y),min(x,z)) by A1,Def1; suppose A2: y <= x & y <= z; then A3: y <= min(x,z) by Th39; thus min(x,max(y,z)) = min(x,z) by A2,Def2 .= max(y,min(x,z)) by A3,Def2 .= max(min(x,y),min(x,z)) by A2,Def1; suppose A4: z <= y & z <= x; then A5: z <= min(x,y) by Th39; thus min(x,max(y,z)) = min(x,y) by A4,Def2 .= max(min(x,y),z) by A5,Def2 .= max(min(x,y),min(x,z)) by A4,Def1; end; theorem max(x,min(y,z)) = min(max(x,y),max(x,z)) proof per cases by AXIOMS:22; suppose A1: x <= y & x <= z; then x <= min(y,z) by Th39; hence max(x,min(y,z)) = min(y,z) by Def2 .= min(max(x,y),z) by A1,Def2 .= min(max(x,y),max(x,z)) by A1,Def2; suppose A2: y <= x & y <= z; hence max(x,min(y,z)) = max(x,y) by Def1 .= x by A2,Def2 .= min(x,max(x,z)) by Th55 .= min(max(x,y),max(x,z)) by A2,Def2; suppose A3: z <= y & z <= x; hence max(x,min(y,z)) = max(x,z) by Def1 .= x by A3,Def2 .= min(max(x,y),x) by Th55 .= min(max(x,y),max(x,z)) by A3,Def2; end; definition let x; func x^2 equals :Def3: x * x; correctness; end; definition let x; cluster x^2 -> real; correctness proof x^2 = x * x by Def3; hence x^2 in REAL by XREAL_0:def 1; end; end; definition let x be Element of REAL; redefine func x^2 -> Element of REAL; correctness by XREAL_0:def 1; end; Lm1: 1*1 = 1; canceled; theorem Th59: 1^2 = 1 by Def3,Lm1; Lm2: 0*0 = 0; theorem Th60: 0^2 = 0 by Def3,Lm2; theorem Th61: a^2 = (-a)^2 proof thus a^2 = --a*a by Def3 .= -(-a)*a by XCMPLX_1:175 .= (-a)*(-a) by XCMPLX_1:175 .= (-a)^2 by Def3; end; theorem (abs(a))^2 = a^2 proof 0 <= a or not 0 <= a; then abs(a) = a or abs(a) = -a by ABSVALUE:def 1; hence thesis by Th61; end; theorem Th63: (a + b)^2 = a^2 + 2*a*b + b^2 proof thus (a + b)^2 = (a + b)*(a + b) by Def3 .= a*(a + b) + b*(a + b) by XCMPLX_1:8 .= a*a + a*b + b*(a + b) by XCMPLX_1:8 .= a*a + a*b + (b*a + b*b) by XCMPLX_1:8 .= a*a + a*b + b*a + b*b by XCMPLX_1:1 .= a*a + (a*b + a*b) + b*b by XCMPLX_1:1 .= a*a + 2*(a*b) + b*b by XCMPLX_1:11 .= a*a + 2*a*b + b*b by XCMPLX_1:4 .= a^2 + 2*a*b + b*b by Def3 .= a^2 + 2*a*b + b^2 by Def3; end; theorem Th64: (a - b)^2 = a^2 - 2*a*b + b^2 proof thus (a - b)^2 = (a + -b)^2 by XCMPLX_0:def 8 .= a^2 + 2*a*(-b) + (-b)^2 by Th63 .= a^2 + -2*a*b + (-b)^2 by XCMPLX_1:175 .= a^2 - 2*a*b + (-b)^2 by XCMPLX_0:def 8 .= a^2 - 2*a*b + b^2 by Th61; end; theorem Th65: (a + 1)^2 = a^2 + 2*a + 1 proof thus (a + 1)^2 = a^2 + 2*a*1 + 1^2 by Th63 .= a^2 + 2*a + 1 by Def3,Lm1; end; theorem (a - 1)^2 = a^2 - 2*a + 1 proof thus (a - 1)^2 = a^2 - 2*a*1 + 1^2 by Th64 .= a^2 - 2*a + 1 by Def3,Lm1; end; theorem Th67: (a - b)*(a + b) = a^2 - b^2 & (a + b)*(a - b) = a^2 - b^2 proof thus (a - b)*(a + b) = (a - b)*a + (a - b)*b by XCMPLX_1:8 .= a*a - b*a + (a - b)*b by XCMPLX_1:40 .= a*a - a*b + (a*b - b*b) by XCMPLX_1:40 .= a*a - b*b by XCMPLX_1:39 .= a^2 - b*b by Def3 .= a^2 - b^2 by Def3; hence thesis; end; theorem Th68: (a*b)^2 = a^2*b^2 proof thus (a*b)^2 = a*b*(a*b) by Def3 .= a*(a*b*b) by XCMPLX_1:4 .= a*(a*(b*b)) by XCMPLX_1:4 .= a*a*(b*b) by XCMPLX_1:4 .= a^2*(b*b) by Def3 .= a^2*b^2 by Def3; end; theorem Th69: (a/b)^2 = a^2/b^2 proof thus (a/b)^2 = (a/b)*(a/b) by Def3 .= (a*a)/(b*b) by XCMPLX_1:77 .= a^2/(b*b) by Def3 .= a^2/b^2 by Def3; end; theorem Th70: a^2-b^2 <> 0 implies 1/(a+b) = (a-b)/(a^2-b^2) proof assume a^2-b^2 <> 0; then (a+b)*(a-b) <> 0 by Th67; then (a+b) <> 0 & (a-b) <> 0; hence 1/(a+b) = (1*(a-b))/((a+b)*(a-b)) by XCMPLX_1:92 .= (a-b)/(a^2-b^2) by Th67; end; theorem Th71: a^2-b^2 <> 0 implies 1/(a-b) = (a+b)/(a^2-b^2) proof assume a^2-b^2 <> 0; then (a+b)*(a-b) <> 0 by Th67; then (a+b) <> 0 & (a-b) <> 0; hence 1/(a-b) = (1*(a+b))/((a-b)*(a+b)) by XCMPLX_1:92 .= (a+b)/(a^2-b^2) by Th67; end; theorem Th72: 0 <= a^2 proof 0 <= a*a by REAL_1:93; hence thesis by Def3; end; theorem Th73: a^2 = 0 implies a = 0 proof assume a^2 = 0; then A1: a*a = 0 by Def3; assume a <> 0; then a < 0 or 0 < a; hence contradiction by A1,Th21,Th22; end; theorem 0 <> a implies 0 < a^2 proof assume 0 <> a; hence 0 <= a^2 & a^2 <> 0 by Th72,Th73; end; theorem Th75: 0 < a & a < 1 implies a^2 < a proof assume 0 < a & a < 1; then a*a < a*1 by REAL_1:70; hence a^2 < a by Def3; end; theorem 1 < a implies a < a^2 proof assume A1: 1 < a; then 0 < a by AXIOMS:22; then a*1 < a*a by A1,REAL_1:70; hence a < a^2 by Def3; end; Lm3: 0 < a implies ex x st 0 < x & x^2 < a proof assume A1: 0 < a; now per cases; suppose A2: 1 <= a; reconsider x = 2" as real number; take x; thus 0 < x; x^2 < 2" by Th75; then x^2 < 1 by AXIOMS:22; hence x^2 < a by A2,AXIOMS:22; suppose A3: a < 1; take x = a; thus 0 < x by A1; thus x^2 < a by A1,A3,Th75; end; hence thesis; end; theorem Th77: 0 <= x & x <= y implies x^2 <= y^2 proof assume 0 <= x & x <= y; then x*x <= x*y & x*y <= y*y by AXIOMS:25; then x*x <= y*y by AXIOMS:22; then x^2 <= y*y by Def3; hence x^2 <= y^2 by Def3; end; theorem Th78: 0 <= x & x < y implies x^2 < y^2 proof assume 0 <= x & x < y; then x*x <= x*y & x*y < y*y by AXIOMS:25,REAL_1:70; then x*x < y*y by AXIOMS:22; then x^2 < y*y by Def3; hence x^2 < y^2 by Def3; end; Lm4: 0 <= x & 0 <= y & x^2 = y^2 implies x = y proof assume A1: 0 <= x & 0 <= y; assume x^2 = y ^2; then x <= y & y <= x by A1,Th78; hence x = y by AXIOMS:21; end; definition let a; assume A1: 0 <= a; func sqrt a -> real number means :Def4: 0 <= it & it^2 = a; existence proof A2: a <= a + 1 by REAL_1:69; A3: (a + 1)^2 = a^2 + 2*a + 1 by Th65 .= a^2 + (a + a) + 1 by XCMPLX_1:11 .= a^2 + a + a + 1 by XCMPLX_1:1 .= a^2 + a + (a + 1) by XCMPLX_1:1; 0 <= a^2 by Th72; then 0 + 0 <= a^2 + a by A1,REAL_1:55; then A4: 0 + a <= a^2 + a + (a + 1) by A2,REAL_1:55; defpred X[real number] means $1 <= 0 or $1^2 <= a; defpred Y[real number] means 0 <= $1 & a <= $1^2; A5: now let x,y such that A6: X[x] and A7: Y[y]; now per cases; suppose x <= 0; hence x <= y by A7; suppose not x <= 0; then x^2 <= y^2 by A6,A7,AXIOMS:22; hence x <= y by A7,Th78; end; hence x <= y; end; consider z such that A8: for x,y st X[x] & Y[y] holds x <= z & z <= y from RealContinuity(A5); take z; thus 0 <= z by A1,A2,A3,A4,A8; assume A9: z^2 <> a; now per cases by A9,AXIOMS:21; suppose A10: z <= 0; then z = 0 by A1,A2,A3,A4,A8; then z^2 = 0*0 by Def3 .= 0; then consider c such that A11: 0 < c and A12: c^2 < a by A1,A9,Lm3; thus contradiction by A1,A2,A3,A4,A8,A10,A11,A12; suppose A13: z^2 < a & not z <= 0; set b = a - z^2; A14: 0/2 = 0; A15: 0 < b by A13,Th11; then 0 < b/2 by A14,REAL_1:73; then consider c such that A16: 0 < c and A17: c^2 < b/2 by Lm3; A18: 2*z <> 0 by A13,XCMPLX_1:6; A19: 0 <= 2*z by A13,Th19; set eps = min(c, b/(4*z)); A20: 0/(4*z) = 0; 0 < 4*z by A13,Th21; then 0 < b/(4*z) by A15,A20,REAL_1:73; then A21: 0 < eps by A16,Th38; eps <= b/(2*2*z) by Th35; then eps <= b/(2*(2*z)) by XCMPLX_1:4; then eps*(2*z) <= b/(2*(2*z))*(2*z) by A19,AXIOMS:25; then eps*(2*z) <= b/2/(2*z)*(2*z) by XCMPLX_1:79; then A22: 2*z*eps <= b/2 by A18,XCMPLX_1:88; eps <= c by Th35; then eps^2 <= c^2 by A21,Th77; then A23: eps^2 <= b/2 by A17,AXIOMS:22; A24: a = z^2 + b by XCMPLX_1:27; A25: (z + eps)^2 = z^2 + 2*z*eps + eps^2 by Th63 .= z^2 + (2*z*eps + eps^2) by XCMPLX_1:1; 2*z*eps + eps^2 <= b/2 + b/2 by A22,A23,REAL_1:55; then 2*z*eps + eps^2 <= b by XCMPLX_1:66; then A26: (z + eps)^2 <= a by A24,A25,AXIOMS:24; z < z + eps by A21,REAL_1:69; hence contradiction by A1,A2,A3,A4,A8,A26; suppose A27: a < z^2 & not z <= 0; set b = z^2 - a; A28: 0 < 2*z by A27,Th21; A29: 2*z <> 0 by A27,Th21; A30: 0 < b by A27,Th11; set eps = min(b/(2*z),z); A31: 0/(2*z) = 0; 0 < 2*z by A27,Th21; then 0 < b/(2*z) by A30,A31,REAL_1:73; then A32: 0 < eps by A27,Th38; A33: a = 0 + a .= z^2 - z^2 + a by XCMPLX_1:14 .= z^2 - b by XCMPLX_1:37; A34: (z - eps)^2 = z^2 - 2*z*eps + eps^2 by Th64 .= z^2 - (2*z*eps - eps^2) by XCMPLX_1:37; eps <= b/(2*z) by Th35; then eps*(2*z) <= b/(2*z)*(2*z) by A28,AXIOMS:25; then A35: 2*z*eps <= b by A29,XCMPLX_1:88; 0 <= eps^2 by Th72; then 2*z*eps - eps^2 <= 2*z*eps - 0 by REAL_1:92; then 2*z*eps - eps^2 <= b by A35,AXIOMS:22; then A36: a <= (z - eps)^2 by A33,A34,REAL_1:92; eps <= z by Th35; then A37: 0 <= z - eps by Th12; z - eps < z by A32,Th29; hence contradiction by A8,A36,A37; end; hence contradiction; end; uniqueness by Lm4; end; definition let a be Element of REAL; redefine func sqrt a -> Element of REAL; coherence by XREAL_0:def 1; end; canceled 3; theorem sqrt 0 = 0 by Def4,Th60; theorem Th83: sqrt 1 = 1 by Def4,Th59; Lm5: 0 <= a implies sqrt a^2 = a proof 0 <= a^2 by Th72; hence thesis by Def4; end; Lm6: 0 <= x & x < y implies sqrt x < sqrt y proof assume that A1: 0 <= x and A2: x < y; A3: 0 <= y by A1,A2,AXIOMS:22; then A4: 0 <= sqrt x & 0 <= sqrt y by A1,Def4; (sqrt x)^2 = x & (sqrt y)^2 = y by A1,A3,Def4; hence sqrt x < sqrt y by A2,A4,Th77; end; theorem 1 < sqrt 2 by Lm6,Th83; Lm7: 2^2 = 2*2 by Def3; theorem Th85: sqrt 4 = 2 by Def4,Lm7; theorem sqrt 2 < 2 by Lm6,Th85; canceled 2; theorem 0 <= a implies sqrt a^2 = a by Lm5; theorem Th90: a <= 0 implies sqrt a^2 = -a proof assume a <= 0; then 0 <= -a & a^2 = (-a)^2 by Th61,REAL_1:26,50; hence sqrt a^2 = -a by Lm5; end; theorem sqrt a^2 = abs(a) proof now per cases; suppose 0 <= a; then sqrt a^2 = a & abs(a) = a by Lm5,ABSVALUE:def 1; hence thesis; suppose not 0 <= a; then abs(a) = -a & a <= 0 by ABSVALUE:def 1; hence thesis by Th90; end; hence thesis; end; theorem 0 <= a & sqrt a = 0 implies a = 0 by Def4,Th60; theorem 0 < a implies 0 < sqrt a proof assume 0 < a; then sqrt a <> 0 & 0 <= sqrt a by Def4,Th60; hence thesis; end; theorem 0 <= x & x <= y implies sqrt x <= sqrt y proof now per cases; suppose x = y; hence thesis; suppose A1: x <> y; assume A2: 0 <= x; assume x <= y; then x < y by A1,REAL_1:def 5; hence sqrt x <= sqrt y by A2,Lm6; end; hence thesis; end; theorem 0 <= x & x < y implies sqrt x < sqrt y by Lm6; theorem Th96: 0 <= x & 0 <= y & sqrt x = sqrt y implies x = y proof assume that A1: 0 <= x & 0 <= y and A2: sqrt x = sqrt y; assume x <> y; then x < y or y < x by AXIOMS:21; hence contradiction by A1,A2,Lm6; end; theorem Th97: 0 <= a & 0 <= b implies sqrt (a*b) = sqrt a * sqrt b proof assume A1: 0 <= a & 0 <= b; then A2: 0 <= a*b by Th19; then A3: (sqrt(a*b))^2 = a*b by Def4 .= (sqrt a)^2*b by A1,Def4 .= (sqrt a)^2*(sqrt b)^2 by A1,Def4 .= (sqrt a*sqrt b)^2 by Th68; 0 <= sqrt a & 0 <= sqrt b by A1,Def4; then A4: 0 <= sqrt(a*b) & 0 <= sqrt a*sqrt b by A2,Def4,Th19; thus sqrt(a*b) = sqrt(sqrt a*sqrt b)^2 by A2,A3,Def4 .= sqrt a*sqrt b by A4,Lm5; end; theorem 0 <= a*b implies sqrt (a*b) = sqrt abs(a)*sqrt abs(b) proof assume 0 <= a*b; then abs(a*b) = a*b by ABSVALUE:def 1; then abs(a)*abs(b) = a*b & 0 <= abs(a) & 0 <= abs(b) by ABSVALUE:5,10; hence thesis by Th97; end; theorem Th99: 0 <= a & 0 <= b implies sqrt (a/b) = sqrt a/sqrt b proof assume A1: 0 <= a & 0 <= b; then A2: 0 <= sqrt a & 0 <= sqrt b by Def4; (sqrt a/sqrt b)^2 = (sqrt a)^2/(sqrt b)^2 & (sqrt a)^2 = a & (sqrt b)^2 = b by A1,Def4,Th69; then 0 <= a/b & 0 <= sqrt a/sqrt b & (sqrt a/sqrt b)^2 = a/b by A1,A2,Th27; hence thesis by Def4; end; theorem 0 < a/b implies sqrt (a/b) = sqrt abs(a) / sqrt abs(b) proof assume 0 < a/b; then (a/b) = abs(a/b) & 0 <= abs(b) by ABSVALUE:5,def 1; then (a/b) = abs(a)/abs(b) & 0 <= abs(a) & 0 <= abs(b) by ABSVALUE:5,16; hence thesis by Th99; end; theorem 0 < a implies sqrt (1/a) = 1/sqrt a by Th83,Th99; theorem 0 < a implies sqrt a/a = 1/sqrt a proof assume A1: 0 < a; then sqrt a <> 0 by Def4,Th60; hence sqrt a/a = (sqrt a*sqrt a)/(a*sqrt a) by XCMPLX_1:92 .= (sqrt a)^2/(a*sqrt a) by Def3 .= (1*a)/(sqrt a*a) by A1,Def4 .= 1/sqrt a by A1,XCMPLX_1:92; end; theorem 0 < a implies a /sqrt a = sqrt a proof assume A1: 0 < a; then sqrt a <> 0 by Def4,Th60; hence a /sqrt a = (a*sqrt a) /(sqrt a*sqrt a) by XCMPLX_1:92 .= (a*sqrt a) /(sqrt a)^2 by Def3 .= (sqrt a*a) /(1*a) by A1,Def4 .= sqrt a/1 by A1,XCMPLX_1:92 .= sqrt a; end; theorem 0 <= a & 0 <= b implies (sqrt a - sqrt b)*(sqrt a + sqrt b) = a - b proof assume A1: 0 <= a & 0 <= b; thus (sqrt a - sqrt b)*(sqrt a + sqrt b) = (sqrt a)^2 - (sqrt b)^2 by Th67 .= a - (sqrt b)^2 by A1,Def4 .= a - b by A1,Def4; end; Lm8: 0 <= a & 0 <= b & a <>b implies (sqrt a)^2-(sqrt b)^2 <> 0 proof assume 0 <= a & 0 <= b & a <>b; then sqrt a <> sqrt b & 0 <= sqrt a & 0 <= sqrt b by Def4,Th96; then (sqrt a)^2 <>(sqrt b)^2 by Lm4; hence (sqrt a)^2-(sqrt b)^2 <> 0 by XCMPLX_1:15; end; theorem 0 <= a & 0 <= b & a <>b implies 1/(sqrt a+sqrt b) = (sqrt a - sqrt b)/(a-b ) proof assume that A1: 0 <= a and A2: 0 <= b and A3: a <>b; (sqrt a)^2-(sqrt b)^2 <> 0 by A1,A2,A3,Lm8; hence 1/(sqrt a+sqrt b) = (sqrt a - sqrt b)/((sqrt a)^2-(sqrt b)^2) by Th70 .= (sqrt a - sqrt b)/(a-(sqrt b)^2) by A1,Def4 .= (sqrt a - sqrt b)/(a-b) by A2,Def4; end; theorem 0 <= b & b < a implies 1/(sqrt a+sqrt b) = (sqrt a - sqrt b)/(a-b) proof assume A1: 0 <= b & b < a; then A2: 0 < a; 0 <= a & b <> a by A1,AXIOMS:22; then (sqrt a)^2-(sqrt b)^2 <> 0 by A1,Lm8; hence 1/(sqrt a+sqrt b) = (sqrt a - sqrt b)/((sqrt a)^2-(sqrt b)^2) by Th70 .= (sqrt a - sqrt b)/(a-(sqrt b)^2) by A2,Def4 .= (sqrt a - sqrt b)/(a-b) by A1,Def4; end; theorem 0 <= a & 0 <= b & a <> b implies 1/(sqrt a-sqrt b) = (sqrt a + sqrt b)/(a- b ) proof assume A1: 0 <= a & 0 <= b & a <>b; then (sqrt a)^2-(sqrt b)^2 <> 0 by Lm8; hence 1/(sqrt a-sqrt b) = (sqrt a + sqrt b)/((sqrt a)^2-(sqrt b)^2) by Th71 .= (sqrt a + sqrt b)/(a-(sqrt b)^2) by A1,Def4 .= (sqrt a + sqrt b)/(a-b) by A1,Def4; end; theorem 0 <= b & b < a implies 1/(sqrt a-sqrt b) = (sqrt a + sqrt b)/(a-b) proof assume A1: 0 <= b & b < a; then A2: 0 < a; 0 <= a & b <> a by A1,AXIOMS:22; then (sqrt a)^2-(sqrt b)^2 <> 0 by A1,Lm8; hence 1/(sqrt a-sqrt b) = (sqrt a + sqrt b)/((sqrt a)^2-(sqrt b)^2) by Th71 .= (sqrt a + sqrt b)/(a-(sqrt b)^2) by A2,Def4 .= (sqrt a + sqrt b)/(a-b) by A1,Def4; end;